ANALISIS SISTEM BALAS JASA TERHADAP PENINGKATAN PT. PN (Persero) XIV PABRIK GULA CAMMING KABUPATEN BONE - Jasmin Daud (AkMen JURNAL ILMIAH, 2009)
Systems analysis recompense to make-up of work productivity of employees of PTPN Persero of Sugar Mill of Camming aim to to know the unidirectional relation among system recompense by employees to improvement peroduktivitas work the employees. System recompense is represent one of factor which must be paid attention to in an company. correct recompensation System gift will influence the storey;level peoduktivitas work the employees. From result analyse obtained by information that recompensation system used have the strong relation to make-up of work productivity of employees of PTPN Persero of Sugar Mill Camming